Between sanity and madness : mental illness from Ancient Greece to the neuroscientific era - Horwitz, Allan V. (New York, NY : Oxford University Press, 2019)
'Between Sanity and Madness' traces the extensive array of answers that various groups have provided to questions about the nature of mental illness and its boundaries with sanity. What distinguishes mental illnesses from other sorts of devalued conditions and from normality? Should medical, religious, psychological, legal, or no authority at all respond to the mentally ill? Why do some people become mad? What treatments might help them recover? Despite general agreement across societies regarding definitions about the pole of madness, huge disparities exist on where dividing lines should be placed between it and sanity and even if there is any clear demarcation at all. Various groups have provided answers to these puzzles that are both widely divergent and surprisingly similar to current understandings.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 14, 2019).
Keywords: Mental illness; Mental illness -- History; Psychiatry -- History; Psychology, Pathological; Neurosciences